Niveles plasmáticos de interleukina 1- â, cortisol, 17- â estradiol y ESG tras fangoterapia y fisioterapia en mujeres postmenopáusicas con artrosis - Untura Filho, Marcos; De Michele, Daniel; Giacomino, Marta; Belderrain, Andrés (Anales de Hidrología Médica, 2008)
Twenty postmenopausal women with knee osteoarthritis were evaluated. These women underwent mud therapy, kinesiology (Maitland method), and low frequency laser. A precise clinical evaluation included a complete radiological study of the affected knee, lab studies and a kinesiotherapeutic study. Initial and final Interleukin 1-â, cortisol, 17-â estradiol serum levels and eritrosedimentation rate (ESR) were performed afterwards that demonstrated quantitative variations that suggest an anti-inflammatory response with a betterment of knee movement (with a greater angle), less time to walk a certain distance (15 linear meters FWT50) an d reduced knee pain according to the Visual Analogical Pain Scale (EVA). Our findings confirm antinflammatory activity in osteoarthritic patients under treatment with local mud and physical therapy.